A Numerical Scheme to Solve Fuzzy Linear Volterra Integral Equations System - A. Jafarian; S. Measoomy Nia; S. Tavan (Journal of Applied Mathematics)
The current research attempts to offer a new method for solving fuzzy linear Volterra integral equations system. This method converts the given fuzzy system into a linear system in crisp case by using the Taylor expansion method. Now the solution of this system yields the unknown Taylor coefficients of the solution functions. The proposed method is illustrated by an example and also results are compared with the exact solution by using computer simulations.